Peran Kuliah Kerja Nyata pada Pelatihan Pembuatan Sabun Cuci Piring untuk Meningkatkan Keterampilan dan Nilai Ekonomi di Desa Beganding Kec Simpang Empat: Pengabdian - Asrika Winana Farida Ayu; Bahzatun Nur Harahap; Rizka Asrina; Tegar Achmad Fariq; Aqwa Naser Daulay (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The training for making dish soap in Beganding Village, Simpang Empat District, was carried out as a form of community empowerment through practical skills that are easy to apply. This research uses a descriptive method by collecting data from observations, interviews, and documentation of activities. The training process was conducted directly so that participants could understand each stage, from selecting materials, mixing, to packaging the products. The results of the activity show an increase in residents' skills in independently producing soap and the emergence of small business opportunities that can support family economy. In addition to providing economic benefits, this activity also encourages the community's self-confidence to utilize new skills as capital to improve welfare. Thus, this training provides dual benefits, namely the increase in community capacity while also paving the way for the development of an economy based on daily needs.